Utilizing REBA Method for Work Posture Analysis of Gallon Shop Employee - Pradityatama, Maharsa; Kurnia, Fikrihadi; Ayu Febriyanti, Nuzha Tri; Salsabila, Ainun; Widisetyo, Shofwan Randyndra (Journal of Industrial Engineering and Innovation, 2024)
Employee productivity, safety, and health are all greatly impacted by work posture, especially in physically demanding settings like water gallon shops. Workers in these stores frequently handle water gallons while performing heavy lifting, repetitive chores, and awkward postures, all of which over time might result in musculoskeletal disorders (MSDs). The Rapid Entire Body Assessment (REBA) method, a well-known ergonomic instrument for assessing the risk levels of work-related musculoskeletal discomfort, will be used in this study to examine the work posture of gallon shop employees. Employee operations like lifting, carrying, and stacking water gallons were observed in order to gather observational data. To assess the degree of risk involved in various tasks, REBA ratings were computed. According to the findings a "Very High Risk" risk level was indicated by the total REBA score of 12, certain postures especially when lifting and carrying big objects fall into high-risk categories and call for prompt ergonomic intervention. This study emphasizes how crucial ergonomic evaluation, therefore REBA method for improving posture at work and safeguarding worker health.